Comparing the Features and Strategies in TV Talk Show Discourse: A Conversation Analysis - Astyanto, Verdian Nugraha (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
Conversation analysis is one of the subfields of discourse analysis that uncovers the intricate dynamics in everyday conversations including in TV talk shows. This study aims to understand how conversation analysis features such as turn-taking strategies, feedbacks, adjacency pairs, and repair mechanisms were used in two different TV talk shows. This study adopted a qualitative content analysis, more specifically the conversation analysis approach. The data collected comes from two interviews of the same person by two different hosts in two different TV talk shows. The results found that there are many similarities and some differences in the conversation analysis features between The Tonight Show Starring Jimmy Fallon and Jimmy Kimmel Live! talk shows. In conclusion, while both shows employs similar strategies, they differ slightly in terms of how it was used and in the overall tone created. These differences point out the unique conversational styles of each host, shaping the viewer's experience and the overall atmosphere of the interviews.